Issues of women and nature in Indonesian novels: A study of feminism - Sumartini, Sumartini; Qomariyah, U'um; Prabaningrum, Dyah (Universitas Mulawarman, 2025)
The purpose of this study is to represent the issues of women and nature contained in the literary works of Indonesian female writers. The data sources for the study came from 5 novels, namely Partikel and Aroma Karsa by Dee Lestari, Geni Jora by Abidah El Khalieqy, Namaku Teweraut by Ani Sekarningsih, and Isinga by Dorothea Rosa Herliany. The data analysis method applied in this study is the semiotic method through heuristic reading. The results of the study show that the problems about women in the author’s view are mystical logic in women, limited exploration of knowledge due to the shackles of religion, the superiority of belief in myths, creating harmful obsession, privileging men over women, women’s insecurity when seeking justice, the absence of validation of women’s greatness, marriage determined by culture results in inhibiting women’s ideals, women are considered subjects who bring trouble/problems, lack of appreciation for young women, inner conflict with their role as mothers, women carrying a mission of peace through marriage, and domestic violence. The environmental problems depicted in the novel are the loss of nutrients in soil, deforestation, water pollution, and forest exploitation.